2009
DOI: 10.1021/bm900516y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics and Adhesion Behavior of Escherichia coli O157:H7: Role of Extracellular Macromolecules

Abstract: Experiments were conducted using enterohemorrhagic Escherichia coli O157:H7 cells to investigate the influence of extracellular macromolecules on cell surface properties and adhesion behavior to quartz sand. Partial removal of the extracellular macromolecules on cells by a proteolytic enzyme (proteinase K) was confirmed using Fourier transform infrared spectroscopy analyses. The proteinase K treated cells exhibited more negative electrophoretic mobility (EPM) at an ionic strength (IS) e 1 mM, a slightly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 77 publications
(243 reference statements)
8
58
1
1
Order By: Relevance
“…No significant differences were found between the total site concentrations on full EPS-cell and on partial EPS-cell surfaces (P N 0.05). The two strains used in this study had more surface site concentrations than another pathogenic E. coli O157:H7 (2.74 × 10 −16 mol cell ) reported by Kim et al (2009b). For each surface site, the decreasing trend for site concentrations was not always observed for the four site types after EPS removal (Table 1).…”
Section: Potentiometric Titrationmentioning
confidence: 68%
See 4 more Smart Citations
“…No significant differences were found between the total site concentrations on full EPS-cell and on partial EPS-cell surfaces (P N 0.05). The two strains used in this study had more surface site concentrations than another pathogenic E. coli O157:H7 (2.74 × 10 −16 mol cell ) reported by Kim et al (2009b). For each surface site, the decreasing trend for site concentrations was not always observed for the four site types after EPS removal (Table 1).…”
Section: Potentiometric Titrationmentioning
confidence: 68%
“…Hence, the different site concentrations of cell walls for the four bacteria could explain the observed variability in the zeta potentials. At the tested pH range (5.6-5.8), the deprotonation of phosphodiester (pK a b 4.0) and carboxylic moieties (pK a b 5.6) primarily contributed to the overall net negative charges of the cells (Kim et al, 2009b). Titration results in Table 1 indicated that the sum of phosphodiester and carboxylic site ) on E. coli after CER treatment may explain the reduced amounts of surface negative charges.…”
Section: Charge Properties Of Bacteria and Soilmentioning
confidence: 97%
See 3 more Smart Citations